Influence of Teacher Empowerment and Global Competitiveness on Teaching Competence - Mccary, Maryjane C. (Randwick International of Education and Linguistics Science Journal, 2025)
Empowered and globally competitive teachers demonstrate higher teaching competence essential for effective and innovative education. This study investigated the influence of teacher empowerment and global competitiveness on teaching competence using a descriptive-correlational research design with regression analysis. The study focused on key dimensions of teacher empowerment, including autonomy, professional development, workload, and access to resources, as well as global competitiveness factors such as technological fluency, international standards, and cultural responsiveness. Teaching competence was evaluated based on knowledge, skills, motivation, professional growth, and self-efficacy. A stratified random sample of 173 secondary school teachers was selected to ensure representation across educational levels and geographic areas. The results revealed no significant differences in teaching competence across demographic variables such as age, educational attainment, years of service, or grade-level assignment. However, teacher empowerment showed a moderately strong positive influence on teaching competence, whereas global competitiveness had a stronger, more significant impact. Together, these factors explained over half of the variance in teaching competence, highlighting their complementary roles in improving instructional effectiveness. Challenges to global competitiveness included technological limitations, resource constraints, curriculum adaptation, and learner diversity. These findings emphasize the need to foster both teacher empowerment and global readiness to develop educators who can meet the evolving demands of education.